APLIKASI DATA MINING UNTUK PENGELOMPOKAN TINGKAT KELARISAN BARANG DENGAN METODE CLUSTERING MENGGUNAKAN ALGORITMA K-MEANS - Arlis, Syafri (Jurnal Ekobistek, 2013)
Salesstrategyrightis veryimportantin businesstobe able toincreasethe value ofsales. Many factors canaffect the level ofsalesof goodsto theresearchmethodsusedwere interviewsandobservation. Inthis paperdiscussedthe use ofdata miningalgorithmsK-means clustering todetermine the level ofbenefitsanitemso thatstockscan bemaintained.Key :data mining, clustering, algorithmsK-means